Existence, uniqueness and stability of random impulsive fractional differential equations. Issue 2 (March 2016) - Vinodkumar, A.; Malar, K.; Gowrisankar, M.; Mohankumar, P.
Abstract: In this article, we study the existence, uniqueness, stability through continuous dependence on initial conditions and Hyers-Ulam-Rassias stability results for random impulsive fractional differential systems by relaxing the linear growth conditions. Finally, we give examples to illustrate its applications.